Spatial Interregional Spread of COVID-19 Through Commuter Interdependence - Andreas Mense; Claus Michelsen (Wirtschaftsdienst)
Abstract The coronavirus has plunged the global economy into crisis. Since the beginning of March, contact and exit restrictions and bans on business activities have been imposed in Germany, schools have been closed, child care has been suspended, and strict hygiene regulations have been issued. In the meantime, the number of reported new infections has been significantly reduced and the German healthcare system does not appear to be overburdened to date. This is one of the reasons why there is now an intensive debate about easing the regulations, which would allow additional economic activity. The article also examines commuter links and the role they have played in the spread of COVID-19 in Germany as well as bad weather conditions and a high population density.